On the Possibility of Detecting Pore Pressure Changes in Marine Sediments Using Bottom Seismometer Data - Sergey Tikhotskiy; Irina Bayuk; Nikita Dubinya (Journal of Marine Science and Engineering, 2023)
This paper is devoted to the detection and analysis of overpressure zones in unconsolidated seafloor sediments using an ocean-bottom seismometer. The methodological aspects of creating a system of anomalous pore pressure zone detection in marine sediments are studied. The aim of this study is to establish the requirements for a pore pressure monitoring system necessary to successfully detect overpressure zones based on seismic response, and to analyze temporal changes in pore pressure distribution. Data from a certain offshore field are used as a basis from which to construct synthetic models of overpressure distribution in marine sediments. Synthetic models are constructed using specially developed rock physics models for unconsolidated saturated media. Seismic responses are calculated for these synthetic models to represent data that otherwise would be obtained from bottom seismometers placed on the seafloor. Resultant seismic responses are studied with respect to the detection of overpressure zones. Possibilities and limitations of bottom seismometer data are discussed. Requirements for the frequency bands of bottom seismometers are formulated based on the results that are obtained.